Exosomal LncRNA LBX1-AS1 Derived From RBPJ Overexpressed-Macrophages Inhibits Oral Squamous Cell Carcinoma Progress via miR-182-5p/FOXO3 - Ai, Yilong; Wei, Haigang; Wu, Siyuan; Tang, Zhe; Li, Xia; Zou, Chen (Frontiers in Oncology, 2021)
Objectives: Macrophage-derived exosomes (Mφ-Exos) are involved in tumor onset, progression, and metastasis, but their regulation in oral squamous cell carcinoma (OSCC) is not fully understood. RBPJ is implicated in macrophage activation and plasticity. In this study, we assessed the role of Mφ-Exos with RBPJ overexpression (RBPJ-OE Mφ-Exos) in OSCC. Materials and methods: The long non-coding RNA (lncRNA) profiles in RBPJ-OE Mφ-Exos and THP-1-like macrophages (WT Mφ)-Exos were evaluated using lncRNA microarray. Then the functions of Mφ-Exo-lncRNA in OSCC cells were assessed via CCK-8, EdU and Transwell invasion assays. Besides, luciferase reporter assay, RNA immunoprecipitation, and Pearson's correlation analysis were adopted to confirm interactions. Ultimately, a nude mouse model of xenografts was used to further analyze the function of Mφ-Exo-lncRNAs in vivo. Results: It was uncovered that lncRNA LBX1-AS1 was upregulated in RBPJ-OE Mφ-Exos relative to that in WT Mφ-Exos. RBPJ-OE Mφ-Exos and LBX1-AS1 overexpression inhibited OSCC cells to proliferate and invade. Meanwhile, LBX1-AS1 knockdown boosted the tumor to grow in vivo. The effects of RBPJ-OE Mφ-Exos on OSCC cells can be reversed by the LBX1-AS1 knockdown. Additionally, mechanistic investigations revealed that LBX1-AS1 acted as a competing endogenous RNA of miR-182-5p to regulate the expression of FOXO3. Conclusion: Exo-LBX1-AS1 secreted from RBPJ-OE Mφ inhibits tumor progression through the LBX1-AS1/miR-182-5p/FOXO3 pathway, and LBX1-AS1 is probably a diagnostic biomarker and potential target for OSCC therapy.